Benign Tumors of the Hand: A Single Institutional Experience - Kumar T, Dinesh; Manavalan, Leo J; Prof, Prof; Kumar K, Senthil; Jayasuriya V, Jayasuriya V (Journal of Neonatal Surgery, 2025)
Tumors involving the hand is a commonly encountered problem, in hand surgery. While most of these pathological diagnoses are benign, rarely malignant lesions are also noted. This study encompasses benign hand tumors encountered by an individual surgeon, and studies their clinical presentations, and histopathological aspects of the disease. This is a retrospective cross-sectional observational study carried out over a period of 1 year conducted at Chettinad Hospital and Research Institute, Chennai. The total samples obtained were 36 and the specimens were chosen randomly until the gathered samples were adequate as per sample size in the study. Histopathological data and clinical data were collected in this study. Of the 36 cases, that were examined and the most common diagnosis was found to be ganglion cyst in 44.44% (n=16) of instances, followed by 22.22% (n=8) cases of Fibroma, Giant cell tumors in 16.66% (n=6) and myxoma in 11.11% (n=4). Schwannoma incidence were noted among 5.55% (n=2) of the study population. There were no incidence of any malignancy among the selected samples. To conclude, Ganglion cysts were the most common benign tumors, but if left untreated these cystic lesions will increase in size causing pain and affect the movement of the region. Complete excision of the lesion should be meticulously be carried out to prevent recurrence...